EFEK PROBIOTIK DAN SELUBIOSE TERHADAP VOLATILE FATTY ACIDS (VFA) DAN NH3 RUMINAL DOMBA GARUT - Supiyani, Atin (LPPM Universitas Negeri Jakarta, 2017)
The composition of feed can improve and optimize the fermentation in sheep rumen. The purpose of this study is to determine the effect of probiotic and cellobiose to rumen fermentation of sheep. Four adult (weight Â±13.5 kg) rumen fistulae sheep were used. The fed given were King grass (Pennisetum purpureum), rice bran and soybean meal that are protected by formaldehyde 0.3% as base feed. Fed treatment were probiotics (0,5% and 1%) and cellobiose (1 ppm and 3 ppm). Parameters measured were pH, N-NH3 and VFA concentration of rumen fluid at 0, 2, 6, 12, and 24 hours after feeding with Completely Randomized Design Factorials 4x5 and continued with Duncan test (Î±=0,05). The ruminal pH range for all treatments between 6.27 - 6.89. The maximum N-NH3 concentration value has been reached at 2 hours after feeding 12.25-18.75 mM. At 0 hours, the total VFA concentration was at an average value of 294.91 mg% and then increased at 2-6 hours reaching its maximum value in the range 661.97-767.70 mg% (p<0.05). The addition of probiotics and cellobiose can optimize rumen fermentation of sheep.